ENHANCING STUDENTS' SPEAKING SKILLS THROUGH THE ESA METHOD: A STUDY OF TENTH GRADERS - Febrianti, Sarwendah; Darsih, Endang; Fadhly, Fahrus Zaman (Indonesian Journal of Learning and Instruction, 2023)
This research investigates the effectiveness of the Engage, Study, Activate (ESA) method in enhancing the speaking skills of tenth-grade students at SMA Negeri 1 Ciawigebang during the 2023/2024 academic year. Employing a pre-experimental design with one group pre-test and post-test, the study involved 30 purposively selected students from a total population of 124. Speaking tests served as instruments for data collection, conducted before and after the treatment. The findings indicate a significant improvement in students’ speaking abilities post-treatment, as evidenced by the increase in mean scores from 68.1 in the pre-test to 73.3 in the post-test. Statistical analysis confirmed that the ESA method positively impacts students’ speaking skills, particularly in terms of accuracy and fluency, as shown by a significant value (p = 0.000 < 0.05). These results suggest that the ESA method is an effective pedagogical tool for fostering speaking competence in high school learners.Keywords: ESA method; teaching speaking; speaking skills; accuracy; fluency; high school students